2018
DOI: 10.1128/jvi.01057-18
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA hsa-miR-324-5p Suppresses H5N1 Virus Replication by Targeting the Viral PB1 and Host CUEDC2

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that are crucial posttranscriptional regulators for host mRNAs. Recent studies indicate that miRNAs may modulate host response during RNA virus infection. However, the role of miRNAs in immune response against H5N1 infection is not clearly understood. In this study, we showed that expression of cellular miRNA miR-324-5p was downregulated in A549 cells in response to infection with RNA viruses H5N1, A/PR8/H1N1, and Newcastle disease virus (NDV) and transfection with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Airborne PM 10 treated A549 cells were infected with New-castle Disease Virus (NDV) – LaSota strain, Highly Pathogenic Avian Influenza virus (H5N1) - A/duck/India/02CA10/2011 strain and vaccine strain PR8 virus (H1N1) – A/PR8/H1N1 virus was generated using the eight plasmid reverse genetics system ( Kumar et al., 2018 ), at respective multiplicity of infection as mentioned in the figures and/or figure legends. PM 10 treated A549 cells were washed by 1X PBS (phosphate-buffered saline) solution and infected with appropriate RNA viruses in serum-free media as per the subsequent experiment then after 60 min, virus containing media was removed from the cells and cells were washed once with 1X PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…Airborne PM 10 treated A549 cells were infected with New-castle Disease Virus (NDV) – LaSota strain, Highly Pathogenic Avian Influenza virus (H5N1) - A/duck/India/02CA10/2011 strain and vaccine strain PR8 virus (H1N1) – A/PR8/H1N1 virus was generated using the eight plasmid reverse genetics system ( Kumar et al., 2018 ), at respective multiplicity of infection as mentioned in the figures and/or figure legends. PM 10 treated A549 cells were washed by 1X PBS (phosphate-buffered saline) solution and infected with appropriate RNA viruses in serum-free media as per the subsequent experiment then after 60 min, virus containing media was removed from the cells and cells were washed once with 1X PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…For example, miR-466i-3p down-regulated the expression of Agap3, Bcl2l11, Vegfa, Arf3, Gsk3b, Psd3, Mylk, Kit, Nedd4l, Efnb2, and Ephb3, while Akt3 could be up-regulated by miR-320-3p, miR-181d-5p, and miR-425-5p, indicating that these miRNA-mRNA networks were complicated and ordered. Previous studies showed that TGF-β signaling pathway (Schultz-Cherry and Hinshaw, 1996;Jones et al, 2005) and JAK-STAT signaling pathway (Kumar et al, 2018) participate in the processes of cell cycle control, differentiation, apoptosis, and innate immunity. Our pathway enrichment analysis results also identified the same pathways, indicating that some of the differentially expressed miRNAs induced by the three PB2-variant viruses may affect the pathophysiological process of influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence hsa-miR-9-5p can be used as a potential target to regulate endocytosis of nSARS-CoV-2 viral RNA and uncontrolled lung inflammation. In FFL A: hsa-miR-9-5p is found to regulats E1A Binding Protein P300 (EP300), a known transcriptional co-activator protein of Hypoxia-Inducible Factor-1(HIF-1) [47]. In FFL B, hsa-miR-324-3p deregulates MYC which is a known transcription factor and oncogene controlling cell cycle progression, cell proliferation, and apoptosis [48].…”
Section: Discussionmentioning
confidence: 99%